Determining the association between hypertension and bone metabolism markers in osteoporotic patients. Issue 24 (18th June 2021) - Hu, Zhuoqing; Yang, Kevin; Hu, Zhihui; Li, Miaosheng; Wei, Hao; Tang, Zheng; Chen, Baitong; Su, Chengbiao; Cai, De; Xu, Jinrong
Abstract : Abstract: The aim of the case study is to examine the association between hypertension and the level of bone metabolism markers in newly diagnosed osteoporotic patients. A cross-sectional study of 518 subjects was done to see the association between hypertension and the level of osteocalcin (OC), bone-specific alkaline phosphatase (B-ALP), Tartrate-resistant acid phosphatase (TRAP.5B), and 25-hydroxy vitamin D (25-OHD). There were 243 (46.9%) osteoporosis patients with hypertension. Both univariate and multivariate analysis have suggested that lower OC and 25-OHD levels were associated with hypertension. The potential confounders-adjusted OC level was significantly lower in hypertensive female group than that in the female without hypertension group [β = -0.20, 95% confidence interval (95% CI) = -0.37 to -0.03, P  = .02 in final adjust model]. The potential confounders-adjusted 25-OHD level was significantly lower in hypertensive male group than that in male without hypertension group (β = -0.34, 95% CI = -0.58 to -0.10, P  = .01 in final adjust model). The B-ALP and TRACP.5B levels were positively associated with hypertension in all patients or subgroup analysis. However, all the correlations had no statistical significance for the B-ALP and TRACP.5B. In conclusion, the hypertension was associated with low level of OC and 25-OHD. Hypertension probably led to low bone turnover, which may be one of the mechanisms of hypertension-related osteoporosis.